The Cost Utility of Virtual Surgical Planning and Computer-Assisted Design/Computer-Assisted Manufacturing in Mandible Reconstruction Using the Free Fibula Osteocutaneous Flap - Kurlander, David E.; Garvey, Patrick B.; Largo, Rene D.; Yu, Peirong; Chang, Edward I.; Hanasono, Matthew M.; Mericli, Alexander F. (Journal of Reconstructive Microsurgery, 2022)
Background The use of virtual surgical planning and computer-assisted design and computer-assisted manufacturing (CAD/CAM) has become widespread for mandible reconstruction with the free fibula flap. However, the cost utility of this technology remains unknown.Methods The authors used a decision tree model to evaluate the cost utility, from the perspective of a hospital or insurer, of mandible reconstruction using CAD/CAM relative to the conventional (non-CAD/CAM) technique for the free fibula flap. Health state probabilities were obtained from a published meta-analysis. Costs were estimated using 2018 Centers for Medicare and Medicaid Services data. Overall expected cost and quality-adjusted life-years (QALYs) were assessed using a Monte Carlo simulation and sensitivity analyses. Cost effectiveness was defined as an incremental cost utility ratio (ICUR) less than the empirically accepted willingness-to-pay value of $50,000 per QALY.Results Although CAD/CAM reconstruction had a higher expected cost compared with the conventional technique ($36,487 vs. $26,086), the expected QALYs were higher (17.25 vs. 16.93), resulting in an ICUR = $32,503/QALY; therefore, the use of CAD/CAM in free fibula flap mandible reconstruction was cost-effective relative to conventional technique. Monte Carlo sensitivity analysis confirmed CAD/CAM's superior cost utility, demonstrating that it was the preferred and more cost-effective option in the majority of simulations. Sensitivity analyses also illustrated that CAD/CAM remains cost effective at an amount less than $42,903 or flap loss rate less than 4.5%.Conclusion This cost utility analysis suggests that mandible reconstruction with the free fibula osteocutaneous flap using CAD/CAM is more cost effective than the conventional technique.
Keywords: computer-assisted design and computer-assisted manufacturing; CAD/CAM; fibula flap; mandibulectomy; cost utility